2021
DOI: 10.17235/reed.2021.7696/2020
|View full text |Cite
|
Sign up to set email alerts
|

Low applicability of the ��six-and-twelve score� in hepatocellular carcinoma treated with drug-eluting beads transarterial chemoembolization

Abstract: applicability of the ''six-and-twelve score" in hepatocellular carcinoma treated with drug-eluting beads transarterial chemoembolization. Rev Esp Enferm Dig 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the original study on the SAT, the score outperformed the BCLC classification and the ALBI score in predictive ability. In external validation studies, the C-Indexes for the SAT ranged between 0.60 and 0.70 (14)(15)(16)(17)(18). However, in all the validation studies, the predictive performance of the SAT was within the same range or somewhat below the performance of the BCLC and ALBI scoring systems (14).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the original study on the SAT, the score outperformed the BCLC classification and the ALBI score in predictive ability. In external validation studies, the C-Indexes for the SAT ranged between 0.60 and 0.70 (14)(15)(16)(17)(18). However, in all the validation studies, the predictive performance of the SAT was within the same range or somewhat below the performance of the BCLC and ALBI scoring systems (14).…”
Section: Discussionmentioning
confidence: 94%
“…It sums the number of tumor nodes and tumor size to obtain a readily applicable stratification system. In the original study, the score showed promising performance, but in an external validation, contrary results were found for the prognosis prediction (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 87%